(untitled) (Jurnal Mekanikal, 2018)
Repetitive cyclic loading of bone during daily course activities is one of the primary causes of bone fracture in humans. Stress and fragility fractures in elderly generation that have been associated with cancellous bone result in reduction of bone strength due to osteoporosis. The aim of this study is to predict the failure of cancellous bone as a function of density and porosity. In this study, two of medial-condlye bovine cancellous bone specimens were loaded in cyclic compression. Monotonic static compressions were tested to determine the boundary conditions of fatigue testing. The loading transferred to the cancellous bone are chosen between 16%-55% of the ultimate stress. The result showed different hysteresis loop with large variation in strain between both medialcondyle of cancellous bone. The two specimens adapt different physiological apparent load until failure. From the results, it can concluded that the same anatomic site with different value of bone density and porosity imply a large effect of the fatigue behavior in relation to modulus degradation and strain changes.